Interaction of HIV-1 reverse transcriptase with a synthetic form of its replication primer, tRNA(Lys,3). - Barat, C (1991)
Using synthetic oligonucleotides, a gene encoding the HIV-1 replication primer, tRNA(Lys,3), was constructed and placed downstream from a bacteriophage T7 promoter. In vitro transcription of this gene yielded a form of tRNA(Lys,3) which lacks the modified bases characteristic of the natural species and the 3' -C-A-dinucleotide. Synthetic tRNA(Lys,3) annealed to a pbs-HIV1 RNA template can prime cDNA synthesis catalysed by recombinant HIV-1 reverse transcriptase. Trans-DDP crosslinking indicates that this synthetic tRNA is still capable of interacting with HIV-1 RT via a 12-nucleotide portion encompassing the anticodon domain. Gel-mobility shift and competition analyses imply that the affinity of synthetic tRNA for RT is reduced. In contrast to earlier observations, synthetic tRNA is readily competed from RT by natural tRNA(Pro). The reduced affinity of synthetic tRNA(Lys,3) for RT is not appreciably affected by mutations in positions within the loop of the anticodon domain. These results would imply that the overall structure of the anticodon domain of tRNA(Lys,3) is an important factor in its recognition by HIV-1 RT. In addition, modified bases within this, although not absolutely required, would appear to make a significant contribution to the enhanced stability of the ribonucleoprotein complex.